HR Practices in the Soccer Industry: Promising Research Arena - Al-Madi, Faisal; Al-Tarawneh, Khalaf Ibrahim; ALSHAMMARI, Marwan Ahmad (International Review of Management and Marketing, 2016)
Human resources (HR) practices have been extensively researched in the management arena, mostly in firms’ context. Yet, there are many other contexts that have enormous potential for more investigation with regard to selection, pay, and turnover intention. One of these contexts is soccer teams, a game that has enormously grown in the last 50 years, and it continues to grow at even larger scales, exceeding all national, religious, and ethnic considerations. This paper considers the possibility of varying ways that HR-related practices may differ in soccer teams depending on factors such as race and tenure. The growing numbers of non-European players in European teams represent a phenomenon that deserves some attention, especially as to how teams in Europe select their players, what factors influence their decisions, how pay is allocated, and what are the mechanisms through which career mobility for soccer professionals occur. In this paper, I present a framework for soccer teams’ HR practices and the theoretical arguments underlying their acts to improve our understanding of these practices in soccer context. My hope is to start a discussion that would continue to develop overtime so we can reach a mature and well-developed framework for the recruitment practices and their outcomes in the soccer context. Keywords: HR Practices, Sport Teams, Hiring, Career Mobility, Soccer Teams HR Strategies. JEL Classifications: M52, M55, O15